Answer:
False
Step-by-step explanation:
You substitute for the second equation.
Then you have to distribute .
Combine like terms.
Hello!
Since we already see an equation that equals y (-2x-4), we can plug that equation into the first to solve for x.
x+4(-2x-4)=19
x-8x-16=19
-7x=35
x=-5
Now that we know the value of x, we will plug it into the second equation to solve for y.
y=-2(-5)-4
y=10=4
y=6
This gives us the answer belowThe correct answer is A) (-5,6)
I hope this helps!
Answer: s = 7
Step-by-step explanation:
27 is simply 9 times 3.
Thus, simply do 63/9 to get 7.
Hope it helps :)
Answer:
140
Step-by-step explanation:
46+94 = 140
Answer:
Mixed martial artist
Step-by-step explanation: